Monitoring Vegetation and Watershed Hydrology Condition with Satellite Imagery in East Kalimantan - Beny Harjadi (Forum Geografi, 2000)
The technical Remote Sensing and Geographic Information System (GIS) had been used to detet vegetation changing of natural forest due to management differences. The target of the study were to determine classification method of satellite imagery in operational scale so that the method can be transfered and applicable for the user. The studied was done at forest concession of PT SLJ-IV (Sumalindo Lestari Jaya-IV), Yanjung Redeb, east Kalimantan Province. Landsat TM with 7 bands and high resolution of 1994 and 1996 were used to differentiate the condition before and after cutting in 1995. The analysis of the Landsats were only in the area where the TPTI (Indonesian Selective Logging System) and TPTI (Indonesian Strip Logging System) system applied. Based on the analysis and field check, it was found that the impact of logging caused decreasing dense forest about 21,3% and inreasing secondary forest around 6,3%. The highest dynamic of each band was band first and the lowest was band second. The differences in the mean of 2 band will give a more clear appearance of the  imagery.